DAMPAK EKONOMIS PENAMBANGAN EMAS BAGI MASYARAKAT MANDOR, KALIMANTAN BARAT - William Chang (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2012)
Gold mining has been an important livelihood for majority of the local people in Mandor, West Kalimantan. The history of gold mining in this area can be traced back to the Dutch period. The luxurious life of local sultans and the Dutch government at that time were supported by the Chinese gold miners. After the independence, gold mining has been contributing to the improvement of socio-economic life of the local people. The local gold miners used their income from gold to start new businesses such as warung or rubber plantation. The local government has prohibited local gold miners to use mercury in their production process, as it can have adverse effect on the environment. This paper describes how the gold mining activity in Mandor has improved the socioeconomic life of the people in Mandor with the cost of environmental degradation. Keywords: Penambang emas, kesejahteraan masyarakat, Mandor